Synthesis and density functional theory studies of azirinyl and oxiranyl functionalized isoindigo and (3Z,3′Z)-3,3′-(ethane-1,2-diylidene)bis(indolin-2-one) derivatives - Khalili, Gholamhossein; McCosker, Patrick M.; Clark, Timothy; Keller, Paul A. (Molecules, 2019)
The design and synthesis of functionalized isoindigo compounds by reaction of isoindigo with (S)-glycidyl tosylate, epibromohydrin, 2-(bromomethyl)-1-(arylsulfonyl)aziridine, and 2-(bromomethyl)-1-(alkylsulfonyl)aziridine in the presence of MeONa proceed under mild conditions in moderate yields. (3Z,3′Z)-3,3′-(Ethane-1,2-diylidene)bis(1-(oxiran-2-ylmethyl)indolin-2-one), with an extended central olefin π-conjugated moiety was also reacted with methyl-oxiranes to give the corresponding N.N″-disubstituted derivative. Calculations with DFT and TD-DFT of hypothetical isoindigo-thiophene DA molecules with various electron withdrawing substituents, including aziridine, oxirane, nitrile, carbonyl, and sulfonate, indicated that the proximity and strength of the functional group have a significant effect on the HOMO, LUMO, vertical excitation energy and oscillator strength of the π-π∗ transitions.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Density functional theory; Donor-acceptor functionalization; Isoindigo alkylation; Organic semiconductor; Time dependent density functional theory